BREAKTHROUGH INNOVATIONS IN IMPLEMENTING THE «SMART CITIES» CONCEPT: EU EXPERIENCE AND UKRAINE'S OPPORTUNITIES - BABENKO, VITALINA; MATSENKO, OLEKSANDR; CHORNA, YAROSLAVA; TROYNIKOVA, VIKTIRIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In today's realities, the introduction of blockchain, IoT, AI technologies is gaining momentum. Of all the modes of transport affected by AI, drones have been the most successful, but restrictive regulations and non-standard traffic rules are forcing European companies to develop their own autonomous prototypes outside the continent. Local unmanned driving licenses lack standardization, which would make it easier for European industry to innovate on a large scale. The lack of clarity in the legal framework on liability in the event of failure, as well as the problem of coordination in the EU, further complicate the problem. Moreover, this problem is relevant for the Ukrainian realities of transport regulation, especially its sphere, which appeals to the transformation of cities into intellectual environments.This article emphasizes the importance of introducing intelligent traffic control systems as a factor in increasing the competitiveness of cities in the long run, highlights the need to standardize protocols for smart systems (V2V, V2I, V2G) to increase the homogeneity and efficiency of the EU transport sector. A separate area is the study of the possibilities of cooperation between Ukraine and the European Union in this area, its inhibitory factors and prospects.
Keywords: innovations; SMART CITIES; transport flows; intelligent environment